McDonaldization of Nigerian Banking Industry in the Post-consolidated Era: An Exploration of the Unavoidable Consequences - Dumbili, Emeka W. (Richtmann Publishing, 2013)
This article explores the McDonaldization of banking operation in Nigeria. In doing so, it brings to light a critical analysis of theincreasing rationalization process in light of a developing economy. McDonaldization thesis has generated serious academicdebate since it was introduced by George Ritzer the American sociologist in 1993. However, it has received seldom attentionamong Nigerian scholars and none to my knowledge has applied it to examine the banking industry which is invariably themost McDonaldized sector in Nigeria. This article therefore, draws on the thesis to explore the increasing rationalizationprocess the sector is undergoing since consolidation and recapitalization exercises began in 2005. The article argues that thesector is McDonaldized and this has engendered efficiency, predictability, calculability and control. The article further arguesthat this McDonaldization process inevitably has led to increasing negative impacts of McDonaldization and concludes bypointing out some remedies.